Breast Reconstruction Combining Lipofilling and Prepectoral Prosthesis after Radiotherapy - Razzouk, Kais (Plast Reconstr Surg Glob Open, 2020)
Prosthetic reconstruction in previously irradiated breasts has been associated with a higher risk of complications. Here we describe the surgical and cosmetic outcome of our breast reconstruction process based on primary fat grafting combined with prosthetic placement. METHODS: In this multicenter retrospective study, 136 patients who underwent mastectomy and external chest wall radiotherapy between 2014 and 2018 were benefited from chest wall lipofilling and silicone implant placement were chosen. Patients were assessed for skin trophicity, thickness, and mobility and were allowed to undergo several lipofilling sessions before implant placement, if required. No patient had >3 lipofilling sessions. Cosmetic outcome was evaluated by the patient, surgeon, and nurse, using a Likert-type ordinal scale. RESULTS: We included 136 patients: 79 patients (58%) received only 1 session of lipofilling before implant placement, 33 (24.6%) had 2 sessions, and 24 (17.4%) had 3 sessions. The volume of the third lipofilling was significantly higher and the volume of the prosthesis of these patients was significantly lower than those of patients undergoing 1 or 2 lipofillings. Reconstruction failure rate was 2.2% (3 patients had explantation); however, all benefited from prosthesis reconstruction a year after the initial procedures. The average satisfaction score was 4.7 out of 5 as evaluated by patients, 4.8 out of 5 by surgeons, and 4.8 out of 5 by nurses. CONCLUSIONS: Primary lipofilling combined with prosthesis placement after radiotherapy is a reconstructive method that yields a satisfactory cosmetic outcome with a low complication rate. Such minimally invasive breast reconstruction approach can be an alternative to flap-based reconstruction.